Disseminated tuberculosis in an immunocompetent young adult involving the middle ear, mastoid, brain, larynx and lungs – a case report - Othman, Iylia Ajmal; Hussin, Ahmad Sahril; Sidek, Dinsuhaimi; Tedin Ng, Ili Nursafra (Faculty of Medicine Universiti Kebangsaan Malaysia, 2023)
Introduction: Tuberculosis (TB) infection still poses worldwide public health issues, infecting almost a quarter of world’s population. Involvement of multiple organs in disseminated disease is particularly rare and often diagnosed late. Case Report: We are reporting a case of disseminated TB infection involving the middle ear, mastoid bone, brain, larynx, and the lungs in an immunocompetent 21-year-old male, likely following reactivation of latent pulmonary TB, 20 years after his initial exposure to maternal pulmonary TB infection. Results: Destructive nature of the disease as seen on high-resolution computed tomography (HRCT) of the temporal bone, without clinical signs of aggressive infection supports our diagnosis of tuberculous otomastoiditis. Magnetic Resonance Imaging (MRI) of the brain was suggestive of right sided multiloculated tuberculous intracerebral abscesses with significant cerebral oedema and right uncal herniation. Chest radiograph showed presence of reticulonodular opacities with bronchiectatic changes over bilateral upper zones and calcified nodules over left upper zone indicating chronic lung infection. The diagnosis of disseminated TB was also made based on our intra-operative findings of cheesy material occupying the right mastoid antrum and the middle ear cavity and moth-eaten appearance of the larynx. The diagnosis was further validated by the histopathological and microbiological results of positive Acid-Fast Bacilli, TB polymerase chain reaction and Gene-Xpert for Mycobacterium tuberculosis. Patient made excellent recovery after 9 months of anti-TB medications. Conclusion: A fullblown disseminated TB in an immunocompetent young adult who had completed the required vaccination is a rare entity. High clinical suspicion and early imagings will expedite delivery of treatment, thus improve prognosis. Although primarily treated with anti-TB medications, some cases may require surgical intervention to obtain tissue to confirm diagnosis, to remove infected sequestrum and when there is clinical evidence of potentially life-threatening complications.